POTENCIAL TURÍSTICO DE LA MICROCUENCA DEL RIO CHIMBORAZO, CANTÓN RIOBAMBA, PROVINCIA DE CHIMBORAZO, ECUADOR - Jácome, Eduardo Muñoz; García, Gustavo Torres (European Scientific Journal, ESJ, 2015)
The countries of the United Nations through the Millennium Development Goals aim to combat poverty, hunger and other problems of humanity, to improve their living conditions. These aspirations are also shared by Ecuador compliance to this Andean country among other things depends on the promotion of tourism. The projection Tourism Plan by 2020 refers to this activity articulating public, private and community efforts will contribute to the sustainable development of their territories. One of those areas is the parish of San Juan, its Development Plan and Land Management, it said that in the watershed of the river Chimborazo there are social, economic, environmental, among other reasons because between productive activities are not considered tourism, because of ignorance about the real value of their natural and cultural resources, so it became necessary to scientifically determine the tourism potential of it as the basis for sustainable tourism planning and management of this high Andean area, helping to improve the improvement their living conditions and good living